Antimicrobial Protection of Pre-irradiated Cotton and Cotton/Polyester Fabrics Printed with Pigment Colours. Issue 4 (November 2013) - Ibrahim, M.A.; Zohdy, M.H.; Salem, A.A.; Hassan, M.S.; El Badawy, L.El Saed
The paper deals with the improvement of the antimicrobial properties of gamma pre-irradiated cotton and cotton/PET blend fabrics, by using of different metal oxides (ZnO and Al2 O3 ) as antimicrobial agents, through the printing process. The antimicrobial properties of the fabrics were evaluated, in terms of the mechanical properties after burying in a soil reach with microorganisms. Moreover, the effect of antimicrobial finishing on the printing properties, in terms of colour strength was investigated. It was found that the antimicrobial properties were enhanced by addition of the metal oxides up to 1% to the pigment printing paste, under pre-irradiation of fabrics up to 5 (kGy) for cotton and blend fabrics. The colour strength (K/S) of printed fabrics was increased by addition of 0.5% of metal oxides and pre-irradiation dose up to 5 (kGy) for cotton fabric and up to (10 (kGy) for blend fabrics. The thermal stability of the printed fabrics was evaluated by thermogravimetric analysis (TGA) technique, which it showed a decreasing in the thermal stability by addition of the metal oxides, varying according to the types of fabrics and metal oxides used.